Plunkett's Internet of Things (IoT) & data analytics industry almanac 2022 : the only comprehensive guide to the IoT, data analytics and M2M industry - Plunkett, Jack W. (Plunkett Research, Ltd., 2022)
The data and areas of interest covered are intentionally broad, ranging from the trends relating to machine communication, robotics, networks and predictive analysis, to emerging technology, to an in depth look at the major for-profit firms within the many industry sectors that make up the IoT and data analytics arena. This book presents a complete overview of the entire IoT and data analytics industry ... This book presents a complete overview of the entire IoT and data analytics industry. For example, you will find trends in the artificial intelligence (AI), machine to machine (M2M) communications, remote sensor and wireless networks and big data and data mining markets, along with easy-to-use charts and tables on all facets of IoT and data analytics in general, from the sales and profits of the providers to projected growth in the industry.